Electrical conductivity of lithium tantalate thin film - S. I. Gudkov; A. V. Solnyshkin; D. A. Kiselev; A. N. Belov (Cerâmica, 2020)
Abstract The electrical conductivity of lithium tantalate thin film on the silicon substrate was studied. The film structure was prepared by RF magnetron sputtering. In general, the current-voltage characteristics were asymmetric and similar to that of a diode. The current-voltage characteristics had several sections associated with various transport mechanisms of current carriers. The main conductivity mechanism was related to the space-charge-limited current. The current-voltage characteristics showed that there was a mismatch between the forward and backward runs. One of the reasons for such behavior is a space charge accumulation due to charge carriers which were injected from the electrode and did not relax.